Perioperative Nimodipine to Improve Cranial Nerve Function: A Systematic Review and Meta-Analysis. Issue 6 (July 2021) - Chorath, Kevin; Go, Beatrice C.; Kaufman, Adam; Brant, Jason; Moreira, Alvaro; Rajasekaran, Karthik
Abstract : Objective: Nimodipine has emerged as a promising strategy for protection of cranial nerves following vestibular schwannoma (VS) resections. Our goal was to conduct a comprehensive analysis of clinical studies to determine the therapeutic efficacy of nimodipine in improving facial nerve and cochlear nerve function. Database reviewed: We searched PubMed, Scopus, Cochrane Clinical Trial Registry, Clinicaltrials.gov, World Health Organization's International Clinical Trials Registry Platform, and EU Clinical Trials Registry to identify clinical studies up to May 11, 2020. Methods: We included studies evaluating perioperative administration of nimodipine as a strategy to prevent or treat facial nerve or cochlear nerve dysfunction following VS resections. Primary outcomes included preservation or recovery of House–Brackman scale for facial nerve function and Hearing and Equilibrium Guidelines for cochlear nerve function at the latest follow-up visit. Secondary outcomes included adverse events and administration strategies of nimodipine. Results: Nine studies (603 patients) met inclusion, of which seven studies (559 patients) were included in the quantitative analysis. Overall, nimodipine significantly increased the odds of cranial nerve recovery compared with controls (odds ratio [OR] 2.87, 95% confidence intervals [CI] [2.08, 3.95]; I 2 = 0%). Subgroup analysis demonstrated that nimodipine was only effective for cochlear nerve preservation (OR 2.78, 95% CI [1.74, 4.45]; I 2 = 0%), but not for facial nerve function (OR 4.54, 95% CI [0.25, 82.42]; I 2 = 33%). Conclusion: Although there is evidence supporting the perioperative role of nimodipine for VS resections, more studies are warranted to help clarify the effects of nimodipine therapy on cranial nerve preservation. Abstract : Supplemental Digital Content is available in the text